The power of leadership in changing social norms in heterogeneous societies - Fabio Galeotti; Jona Krutaj; Marie Claire Villeval (Proceedings of the National Academy of Sciences, 2026)
Abandoning detrimental social norms is complex due to the strong pressure to conform. We examine how leaders can guide norm change in heterogeneous societies where individual preferences evolve at different rates. Inspired by the model and experimental design of [J. Andreoni, N. Nikiforakis, and S. Siegenthaler, Proc. Natl. Acad. Sci. U.S.A. 118 , e2014893118 (2021)], we conduct a large-scale laboratory experiment in which we manipulate the speed at which preferences change within a society and introduce leaders with different, evolving preferences. Without leaders, a minority of citizens with rapidly changing preferences cannot overturn an existing norm in a society where most individuals have slow-changing preferences. When fast-changing citizens form the majority, norm change occurs in most groups, but at high welfare costs. In contrast, exogenously selected leaders are highly effective at coordinating expectations and shifting heterogeneous societies toward a more efficient norm—at lower welfare costs and regardless of the underlying distribution of preference evolution across individuals. However, the timing of norm change depends on whether leaders prioritize their preferences (autocratic leadership) or those of the majority (democratic leadership). A follow-up experiment shows that peer-to-peer communication encourages leaders to adopt a more democratic leadership style. These results highlight the pivotal role of leadership in driving norm change and the importance of public voice in shaping leaders’ behavior.